Wage inequality and job insecurity among permanent and contract workers in India: evidence from organized manufacturing industries - Amit K. Bhandari; Almas Heshmati (Institute for the Study of Labor (IZA), 2006)
Since the early 1990s, the employment structure of organised manufacturing industries in India has undergone substantial changes with the steep rise in the use of contract workers in place of permanent workers. This process has led to increased wage inequality, discrimination as well as the concern of job insecurity in the labour market. We focus on the wage inequality between permanent and contract workers, since contract workers earn substantially lower wages than their counterpart. The study uses data at the individual level from a recent labour survey of organised manufacturing industries in India. The lower wage earned by contract worker is largely due to cost cutting, rather than differences in labour productivity. The issue of job insecurity has been modeled in form of a binary logistic model. The factors affecting job security are divided as productivity related attributes like level of education, skill etc. and institutional attributes such as labour market rules and regulations, union membership etc. Contrary to the general expectation the study finds that permanent workers are more concern of job insecurity than contract workers.
Keywords: J70; J31; J60; 330; job security; discrimination; wages; decomposition; permanent and contract workers; manufacturing